RETRACTED: CSF p-tau as a potential cognition impairment biomarker in ALS - Gong, Zhongying; Gao, Lina; Lu, Yi; Wang, Zhiyun (Frontiers in Neurology, 2022)
Background: Cerebrospinal fluid (CSF) and serum tau (t-tau, p-tau) are potential biomarkers for neurodegeneration in Alzheimer disease (AD), but their role in amyotrophic lateral sclerosis (ALS) is unclear. Objectives: The aim of our study was to evaluate CSF and serum p-tau and t-tau in patients with ALS and to analyze the correlation and clinical parameters between them. Methods: CSF and serum samples were obtained from 90 patients with ALS, 48 OND, and 20 with ALS mimic (AM) diseases. The levels of p-tau and t-tau in the CSF and serum were assessed with a enzyme-linked immunosorbent assay, and disease progression parameters, including the duration, the ALSFRS-R score, DPR, the UMN score, the MMSE score, the MoCA score, and the ECAS results, were analyzed by registered neurologists. Statistical analyses were performed using Prism software. Results: Compared with controls, patients with ALS displayed significantly lower levels of CSF p-tau and p-tau:t-tau ratio. The CSF p-tau level in patients with ALS and cognition impairment was higher than that in patients with ALS who did not have cognition impairment. CSF p-tau level was negatively correlated with MMSE, MoCA, ECAS total score and the specific score of ECAS in patients with ALS and cognition impairment. Conclusions: The CSF p-tau level and p-tau:t-tau ratio were lower in patients with ALS than patients with OND and AM. Results suggest that CSF p-tau may be used as an index of cognition impairment in patients with ALS.